Implementation of Problem- Based Learning Model Assisted by E-Modules on Students' Critical Thinking Ability - Rahmat, M Rahmat; Arip, Asep Ginanjar; Nur, Sofyan H. (JPI (Jurnal Pendidikan Indonesia), 2020)
Education is a significant factor to shape human beings as a whole. The ability to think for humans plays an important role to develop information. The issue of lack of ability to think critically in Sahida Lemah Abang Vocational High School needed to be addressed. One learning model that can be utilized to guide students to think critically is Problem Based Learning (PBL) using an e-module as the resource of learning material. The study aims to examine the implementation of Problem Based Learning model using e-module and its influence on students' critical thinking ability.Â  This study used a quasi-experiment with nonequivalent control group design as its research design. In using the research design, two observations have been conducted; one was before the experiment called Pre-Test (O1) and one after the experiment of this study called the post-test (O2). There are two samples in this study; one is the experimental group and the other is the control group. The study was done in Sahida Lemah Abang Vocational High School. The data was gathered by using tests and observation sheets of the learning process. The result in this study shows averagely that the implementation in each of the learning stages has gained 95.7% which is in the category of very good value. The most significant difference is from the fifth indicator "developing strategy and tactic", n gain of experimental class and control class is 5.83 and 0.23 respectively. As the result of the hypothesis test is Sig. 0.035 which means that there is a significant difference in students' ability to think critically between the students in the experimental class and the control class, the students in the experimental class think more critically than the students in the control class.